Processes of Making : Algorithmic Methods in Architectural Practise - Kathrin M. Wiertelarz (Kassel University Press GmbH_Legacy, 2016)
Computational methods in design practice are powerful tools for solving highly constrained problems, and for refining existing design solutions. Algorithmic tools can help in the design process and significantly extend the range of possible solutions. The automation of many routines and the repetitive activities of the design process both provide a release for an architect, allowing him or her more time to think about the design. The main goal of this research study is to explore the potential of parametric modeling for dynamically resolving and controlling the particular conditions of the design and manufacturing processes. The vision is to be able to approach this process in general by way of several design systems for the construction of architectural models and, finally, to build up life-sized solutions.